A general lemma for fixed-point theorems involving more than two maps in D-metric spaces with applications - B. C. Dhage; Smrati Arya; Jeong Sheok Ume (International Journal of Mathematics and Mathematical Sciences)
A general procedural lemma for fixed-point theorems for three and four maps in a D-metric space is proved, and it is further applied for proving the common fixed-point theorems of three and four maps in a D-metric space satisfying certain contractive conditions.